Collaborative compromise of two-dimensional materials in sodium ion capacitors: mechanisms and designing strategies. Issue 13 (12th March 2021) - Jiang, Yingjun; Liu, Zhifang; Guo, Songtao; Wang, Libin; Li, Yaqian; Hu, Xianluo
Abstract : This review provides a comprehensive summary of the research progress of emerging 2D materials in sodium ion capacitors. Abstract : Sodium ion capacitors (SICs) have received increasing attention because of the abundant sodium source and low-cost sodium salts. Generally, SICs are hybrid systems consisting of a battery-type anode (or cathode) and a capacitor-type cathode (or anode). The former provides a high energy density, while the latter contributes to a high power output. The kinetics imbalance and capacity mismatch typically exist between battery-type electrodes (with slow kinetics and high capacity) and capacitor-type electrodes (with fast kinetics and low capacity). These issues could be addressed by structural design or surface modification of electrode materials. Two-dimensional (2D) nano-engineering has been recently developed for structural design of high-efficiency electrode materials. 2D materials provide more electrochemically active sites due to their high specific surface areas for high-capacity electrode materials, and facilitate faster electrolyte-ion diffusion kinetics for battery-type electrode materials because of short solid-state diffusion time. Although 2D materials are extensively reported, there has so far been no particular overview about the structure–activity relationship, mechanisms, and designing strategies of emerging 2D materials in SICs. In this review, the recent development of 2D materials in SICs and the detailed impact of 2D nanoengineering for sodium storage are summarized. Rational design of 2D nanostructured materials is proposed to tackle the challenges of SICs. Moreover, current challenges and future perspectives towards 2D materials-based SICs are discussed. This review is expected to provide inspirations to rationally design 2D materials for high-performance SICs.